Factors Influencing Online Video Advertising That Have an Impact on Brand Awareness, Brand Image, and Purchase Intention - Halley Putri Kharisma; Kezia Melodia Adiprasetya; Syafi Fabio Djohan; Willy Gunadi (Budapest International Research and Critics University, 2022)
Along with the development of the evolution of social media, online video marketing can be accessed easily. Therefore, several aspects are needed so that online video advertising can be attractive to consumers. This study investigates the impact of entertainment, informativeness, credibility, customization, and irritation on ad values that affect brand awareness and brand image, which leads to purchase intention in online video advertising. Data was collected through online questionnaires given to 150 people who live in Java who are interested in buying products or services because they watch advertisements on YouTube. This study uses Structural Equation Modeling (SEM) with the SmartPLS. The results show that entertainment, informativeness, credibility, customization have positively affected ad value, while irritation has negatively affected ad value on YouTube. On the other hand, ad value through YouTube affected both brand awareness and brand image. Brand image positively affected purchase intention, however brand awareness did not affect purchase intention.